Web-based information and support for patients with a newly diagnosed neuroendocrine tumor: a feasibility study - Bouma, Grietje (Support Care Cancer, 2017)
PURPOSE: Patients with a neuroendocrine tumor (NET) frequently experience physical and psychosocial complaints. Novel strategies to provide information to optimize supportive care in these patients are of interest. The aim of this study was to examine whether the use of a web-based system consisting of self-screening of problems and care needs, patient education, and self-referral to professional health care is feasible in NET patients and to evaluate their opinion on this. METHODS: Newly diagnosed NET patients were randomized between standard care (n = 10) or intervention with additional access to the web-based system (n = 10) during 12 weeks. Patients completed questionnaires regarding received information, distress, quality of life (QoL), and empowerment. The intervention group completed a semi-structured interview to assess patients’ opinion on the web-based system. RESULTS: The participation rate was 77% (20/26 invited patients) with no dropouts. The use of the web-based system had a negative effect on patients’ perception and satisfaction of received information (range Cohen’s d −0.88 to 0.13). Positive effects were found for distress (Cohen’s d 0.75), global QoL (subscale European Organization for Research and Treatment of Cancer (EORTC) QLQ-C30, Cohen’s d 0.46), resolving problems with social functioning and finding information (subscales EORTC QLQ-GINET 21, Cohen’s d 0.69, respectively, 1.04), and feeling informed (subscale empowerment questionnaire, Cohen’s d 0.51). The interview indicated that the web-based system was of additional value to standard care. CONCLUSIONS: Use of this web-based system is feasible. Contradictory effects on informing and supporting NET patients were found and should be subject of further research. TRIAL REGISTRATION: NCT01849523